Physicochemical and Microbiological Characterization of Cookies Made with Fruit Waste Flour (Research, Society and Development, 2019)
The present study aimed to formulate flour-based cookies from passion fruit, pineapple and melon residues, and analyze them for physicochemical and microbiological parameters. The cookies were formulated with different concentrations of fruit residue flour (FRF), with 10% FI, 20% FII and 30% concentration. The samples were characterized according to the parameters: Water / moisture content (%), water activity (Aa), lipids (%), color, soluble solids content (SST), titratable acidity (TA) and pH. In addition, microbiological analyzes were performed, evaluating them for the presence of: total coliforms, molds and yeast. The results of the physicochemical analyzes found for FI, FII and FIII were respectively: The water / moisture content was less than 14% for all samples and the water activity presented values below 0.6, in compliance with current legislation. . The lipid content of the samples showed no significant difference. In the color analysis, we obtained results that indicated that all the samples tended to have a darker coloration, as well as the FI sample showed favorable values for a reddish and yellowish coloration compared to the other cookies. Soluble solids showed values of 4.17, 4.13 and 4.40 ° Brix respectively. The acidity content of the samples was 5.16, 5.16 and 6.45. The pH was 6.36, 6.10 and 6.01. Regarding microbiological analysis, the biscuits presented adequate sanitary hygienic conditions, indicating good manufacturing practices and good quality of the raw materials used. It was concluded that the fruit waste cookies presented very satisfactory physicochemical and microbiological parameters, meeting the values determined by the current legislation, as well as results similar to researches that used organic residues for food production.